Bovine spongiform encephalopathy: epidemiology and diagnosis - La Bonnardière, Claude (Agricultura Scientia, 2020)
Bovine spongiform encephalopathy (BSE) belongs to the group of of so-called “prion diseases”. These fatal neurodegenerative diseases are characterised by long incubation periods, and in the clinical phase by the presence of amyloid deposits, in the central nervous system, of an abnormally folded form of a host protein, PrP. BSE emerged in the UK in 1986, probably through feeding cattle with animal proteins from infected carcasses, possibly those of scrapie-infected sheep. Not only BSE was exported to other countries in Europe via MBM and live cattle, but it was most probably the origin in humans of a variant of Creutzfzeld-Jacob disease (vCJD), first described in Great Britain in 1996. vCJD incidence is regularly increasing, most cases being among UK citizens. Due to a very difficult clinical diagnosis, BSE incidence in countries outside UK has been and still is most probably underestimated. Some countries (Germany, Spain, Italy) have ignored indigenous BSE cases until 2001, when EU directives implemented systematic tests for over 30 months cattlle entering the food chain. Present tests approved by the EU rely upon detection of abnormal PrP (proteinase K resistant) in the brain of cattle after slaughter. These tests provide a reasonable precautionary measure for protection of human health (the best precaution being the removal of SRM from carcasses), but cannot help much the eradication of BSE. Control and eradication of BSE will depend on specific and sensitive diagnostic tests that could be applied on live animals early in infection. Several recently published results give some hope that such early diagnostic tests might be available in a near future.
Keywords: bovine spongiform encephalopathy; epidemiology; diagnosis; test